EVALUATION OF AGE RELATED CHANGES IN LUMBAR SPINE IN SAUDI ARABIAN ADULT POPULATION: USING MAGNETIC RESONANCE IMAGES - ALI HASSAN A. ALI; ABDULWAHAB A. ABUDERMAN; OMAR O.SERHAN (International Journal of Pharma and Bio Sciences, 2015)
The main objective of our study was to investigate the frequency of lumbar spine degeneration in subjects with low back pain using magnetic resonance images. We evaluated magnetic resonance imaging (MRI) results from 210 patients complaining low back pain for age-related degeneration in the lumbar spine. In this study, 210 adult cases ranging between 18 - 90 years of age were included. The cases were classified into 3 groups; young age group (18 - 35 years old) (66 cases), middle age group (36 - 55 years old) (75 cases) and old age group (56 - 90 years old) (69 cases).Their MRI scans were performed in the department of radiology, King Khalid Hospital, Al Kharj and studied for any age related changes. The most common feature observed in young age group was reduced disc height followed by reduced signal intensity and modic type changes. In the middle age group reduced signal intensity was the most common feature followed by modic type changes. The reduced signal intensity and modic type changes were more frequently seen in the old age group. Degenerative findings in the lumbar spine, suggesting degeneration, were common in symptomatic subjects. These results provide normative data for evaluating patients with degenerative lumbar diseases in Saudi adult symptomatic subjects.